Wilm's Tumor-Collaborative Approach is needed to Prevent Tumor Upstaging and Radiotherapy Delays: A Single Institutional Study - Wani, Shaqul Qamar; Khan, Talib; Wani, Saiful Yammin; Lone, Mohammad Maqbool; Afroz, Fir (Indian Journal of Medical and Paediatric Oncology, 2019)
Context: Successful management of Wilm's tumor (WT) necessitates meticulous attention for proper staging and collaborative effort for its optimal management. Aims: The aim of the study was to observe the patterns of WT. Settings and Design: This study was a single-institutional retrospective study. Subjects and Methods: Twenty-three WT case records were analyzed over 6 years and the data collected were interpreted as number, percent, mean ± and standard deviation with regard to clinicodemographic aspects, staging, and diagnostic modality and treatment options. Results: Mean age was 3.97 ± 2.67 years with maximum number in the 2–5-year age group. Males slightly dominated the number, and majority cases were from the rural area. The major clinical presentation was abdominal mass followed by abdominal pain, fever, vomiting, hematuria, and urinary retention. Left laterality was common and single bilateral WT was seen. Majority of tumors were >10 cm in their largest dimensions. Most WT presented in Stage III followed by Stage I and IV. One was a recurrent tumor. Conclusion: WT was usually diagnosed at the locally advanced or metastatic stages; hence, the comprehensive collaborative approach will help to manage the patients optimally and avoid tumor upstaging and radiotherapy delays. Besides awareness at community level is needed to pick up the disease at the earlier stage to have a better outcome in the form of disease control and disease-free survival.
Keywords: Abdominal mass; nephroblastoma; radiotherapy delays; tumor upstaging; Wilm's tumor